Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1095/biolreprod67.4.1232
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sertoli-Sertoli Tight Junctions to Ectoplasmic Specialization in Conventional and En Face Views

Abstract: Ectoplasmic specializations are actin filament-endoplasmic reticulum complexes that occur in Sertoli cells at sites of intercellular attachment. At sites between inter-Sertoli cell attachments, near the base of the cells, the sites are also related to tight junctions. We studied the characteristics of ectoplasmic specializations from six species using conventional views in which thin sections were perpendicular to the plane of the membranes, we used rare views in which the sections were in the plane of the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…The mammalian spermatids attach to the Sertoli cell membrane through the apical ES [66]. The F-actin-based ES forms around developing spermatids inside the Sertoli cell [13].…”
Section: Resultsmentioning
confidence: 99%
“…The mammalian spermatids attach to the Sertoli cell membrane through the apical ES [66]. The F-actin-based ES forms around developing spermatids inside the Sertoli cell [13].…”
Section: Resultsmentioning
confidence: 99%
“…Although the bands of tight junctions, adherens junctions, and desmosomes support each other functionally through interactions with scaffolding proteins and the cytoskeleton, these different types of cell -cell contact are physically separate from each other in most polarized epithelia (Wong et al 2008). However, at the BTB in Sertoli cells, the tight junctions and specialized adherens junctions (basal ectoplasmic specialization and basal tubulobulbar complex), as well as the basal gap junctions and desmosome-like junctions are all intermingled with each other (Russell & Peterson 1985;Parreira et al 2002;Wong et al 2008). In addition to the tight junctions, the basal ectoplasmic specialization (Yan & Cheng 2005;Lie et al 2006;Yan et al 2007) and desmosome-like junctions (Li et al 2009) appear to be integral, functional components of the BTB.…”
Section: Blood -Testis Barriermentioning
confidence: 99%
“…The ectoplasmic specialization (ES) is a specialized adhesion junction found in Sertoli cells at sites of attachment to elongated spermatids or neighboring Sertoli cells in the testes20. Spermiation failure can be indicative of disruption of ES21.…”
Section: Resultsmentioning
confidence: 99%
“…As expectedly, the sizes and weights of the testes in Mkrn2 knockout mice were lower than those in normal mouse testes. TEM analysis revealed that impaired ES structure in Mkrn2 knockout mice203031. ES is mainly characterized by the presence of a unique junction plaque containing parallel actin bundles sandwiched between the plasma membrane of Sertoli cells and affiliated endoplasmic reticulum3233.…”
Section: Discussionmentioning
confidence: 99%